IMPLEMENTATION OF CUSTOMER RELATIONSHIP MANAGEMENT IN OPERATIONS EFFORTS TO INCREASE SALES - Ilham Ramanda; Herman Saputra; Sri Rezki Maulina Azmi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
The development of information technology today facilitates human work as a medium to run a business or business. Syafri's shop is a shop that serves various kinds of basic needs needed by the people in Kisaran City. The company in the food sector is still implementing manual sales. With today's tight business competition, it is necessary to create an online sales system at Syafri's Store by applying the Customer Relationship Management (CRM) method which intends to know customer needs and customer desires to find out good relationships with customers. The purpose of this study is to find out what consumers are asking to stay loyal to buy products and to increase sales at Syafri Stores by implementing a Customer Relationship Management system. Meanwhile, in making this system a responsive web-based system with PHP and MYSQL programming languages as databases.